Mammoth science : (with a little help from some elephant shrews) - Macaulay, David (DK, 2020)
A troupe of illustrated, curious mammoths explore fun facts about physics, chemistry, and biology. They ask questions and research things like why objects float, what gives mammoths their mass, and what goes on inside a living cell. Includes a glossary.